Realization of Lieb lattice in covalent-organic frameworks with tunable topology and magnetism - Bin Cui (Nature Portfolio, 2020)
Although artificial Lieb lattices have been recently synthesized, the realization of a Lieb lattice in a real material is still challenging. Here the authors use tight-binding and first principle calculations to predict tunable topology and magnetism in recently discovered two-dimensional covalent-organic frameworks.